2022
DOI: 10.1111/ctr.14698
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of right lobe donors with BMI≥30 for living donor liver transplantation

Abstract: Background: Donor BMI above 30 is generally considered contraindication for donor hepatectomy. We compared the donor outcomes based on BMI threshold and weight loss.Patients and methods: All potential donors were identified and data were collected retrospectively. Steatosis was assessed based on liver-spleen Hounsfield unit difference and absolute liver intensity values. We compared BMI≥30 (n = 53) and BMI < 30 (n = 64) donor outcomes. Donors with weight loss (WL) prior to surgery were also analyzed separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The incidence of donor wound infection increased as BMI exceeded 30 kg/m 2 ; however, it was not associated with significant morbidity [420]. A comparison of the outcomes of donors and recipients between the BMI less than 30 kg/m 2 group and the BMI above 30 kg/m 2 group without steatosis revealed no differences between both groups [421][422][423]. Obesity has been defined as a BMI > 30 kg/m 2 in the West, while a BMI > 25 kg/m 2 in the Asia-Pacific region is regarded as obesity [424].…”
Section: Donor Selectionmentioning
confidence: 93%
“…The incidence of donor wound infection increased as BMI exceeded 30 kg/m 2 ; however, it was not associated with significant morbidity [420]. A comparison of the outcomes of donors and recipients between the BMI less than 30 kg/m 2 group and the BMI above 30 kg/m 2 group without steatosis revealed no differences between both groups [421][422][423]. Obesity has been defined as a BMI > 30 kg/m 2 in the West, while a BMI > 25 kg/m 2 in the Asia-Pacific region is regarded as obesity [424].…”
Section: Donor Selectionmentioning
confidence: 93%
“…With respect to guidelines, all obese donors were evaluated for comorbidities before inclusion-especially hepatic steatosis-and had similar preoperative characteristics to non-obese donors in all studies. No significant differences were observed in the rate of complications at 30 days [ 20 22 ] except for wound complications.…”
Section: Obese Donors’ Outcomesmentioning
confidence: 99%
“…Findings of interest in this subgroup included higher rates of grade 1 or 2 steatosis and biliary complications. [ 22 ] A recent meta-analysis of 6 studies included 102 obese donors who achieved a mean reduction in BMI of -2.08. Results were promising, with 91.2% achieving reduction/resolution of steatosis, a mean difference of -21.2% steatosis on biopsy, and similar post-operative outcomes to the control group with no steatosis.…”
Section: Pre-transplant Bmi Optimizationmentioning
confidence: 99%
“…These interventions usually take 4-12 wk leading to loss of valuable time and resources for donors and recipients. 2,3 Lately, there has been a rise in the use of living donors with BMI >30 kg/m 2 with conflicting reports on the associated outcomes in the literature. A recent study observed a significant increase in wound infection rates in donors with obesity, while Dirican et al 4 noted significantly higher rates of Clavien-Dindo grade IIIb complication in extended criteria donors defined as either BMI ≥30 kg/m 2 , age >55 y, or remnant liver volume <30%.…”
mentioning
confidence: 99%
“…5,6 In contrast, others have found no difference in the rates of complications, length of hospital stay (LOS), operative time, or recovery after donation from donors who were overweight or obese. 2,7 Currently, available literature is based on single center or pooled data with small sample size and shorter duration of follow-up. There has been no investigation of national US data on the impact of donor BMI on donor and recipient outcomes.…”
mentioning
confidence: 99%